Growing Digital Roots: A Community of Practice Approach to Technology‐Infused Graduate Student Development. (7th October 2020) - Silva, Steve; Vyn, Reuben; Gatewood, Rachel; Colombo, Mariana; Saichaie, Kem
Abstract: This chapter describes a program where graduate students serve as instructional technology consultants on educational projects that enhance the student‐learning experience. In the process, they develop skills to prepare them for a variety of academic and professional settings.